The Implementation Of Authentic Assessment Based On The 2013 Curriculum For The Student Of 8th Grade At SMP Negeri 3 Colomadu - Salamah, Umi, Dra. Siti Zuhriyah A., M.Hum (2016)
This study aims at describing the implementation of authentic assessment based on the 2013 curriculum especially in speaking for knowledge and skill for the student 8th grade at SMP Negeri 3 Colomadu. This research is descriptive qualitative research. The subject of the research is the student of SMP Negeri 3 Colomadu at 8th grade. The object of this research is the implementation of authentic assessment in speaking for knowledge and skill of the student of 8th grade at SMP Negeri 3 Colomadu. The method of collecting data are observation, interview and documentation. The data are analyzed descriptive by using the principle assessment in the 2013 curriculum and the theory of authentic assessment by O'Malley. From the finding it can be said that the teacher uses authentic assessment to assess speaking of the student 8th grade. The research finding is describe in line with the problem statement. The authentic assessment is implemented through classroom activities and teacher's instruction. There are some ways used by the teacher namely game, role play, story telling and performance. The techniques used by the teacher is different, but both of knowledge and skill, those techniques is integrated in the performance of the students. So, it can be said that the techniques used by the teacher is appropriate with the principle assessment in the 2013 curriculum and also appropriate with O'Malley theory. The researcher also finds the techniques that the teacher used to score the students' abilities in speaking. The teacher uses rubric score. An ideal rubric score should covers the aspects, criteria, and scores. The rubric score used by the teacher in assessing speaking is different both knowledge and skill but, both of them is parallel. There are two criteria of students. The student's speaking can achieve the minimal achievement standard (KKM) determined by the school that is 78 and some others student cannot achieve it.